MIMIC-IV, a freely accessible electronic health record dataset - Johnson, Alistair E. W.; Bulgarelli, Lucas; Shen, Lu; Gayles, Alvin; Shammout, Ayad; Horng, Steven; Pollard, Tom J.; Hao, Sicheng; Moody, Benjamin; Gow, Brian; Lehman, Li-wei H.; Celi, Leo A.; et al. (Scientific data, 2023)
Digital data collection during routine clinical practice is now ubiquitous within hospitals. The data contains valuable information on the care of patients and their response to treatments, offering exciting opportunities for research. Typically, data are stored within archival systems that are not intended to support research. These systems are often inaccessible to researchers and structured for optimal storage, rather than interpretability and analysis. Here we present MIMIC-IV, a publicly available database sourced from the electronic health record of the Beth Israel Deaconess Medical Center. Information available includes patient measurements, orders, diagnoses, procedures, treatments, and deidentified free-text clinical notes. MIMIC-IV is intended to support a wide array of research studies and educational material, helping to reduce barriers to conducting clinical research. Measurement(s) Homo sapiens Technology Type(s) Electronic Health Record Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment hospital Sample Characteristic - Location Commonwealth of Massachusetts